Estudo comparativo das técnicas de micro resíduo de carbono (ASTM D4530) e termogravimetria na análise de biodiesel - Franco, Pedro Ivo Brandão e Melo (2012)
The thermogravimetry has emerged to be an alternative technique for the analysis of biodiesel due to the rapidly methods, sensitivity and accuracy. Because of different characteristics between biodiesel and petroleum products, is difficult to adapt standard methods as in many cases the result dimension is quite distinct by capability of equipment detection. The micro residue of carbon test is one of the techniques which do not accomplish the biodiesel requirements. There is a deviation between national legislation and stipulated technical standard, thru ASTM D4530 for petroleum samples, the test should be applied with the residual of 0,10% (w/w) once previously distilled to remove 90% (v/v) of the total volume. Therefore thermogravimetry turn as an alternative for essay of micro carbon residue based on the results of this study which perform in biodiesel analysis and it has several advantages.